Effects of pluviometric precipitation on agricultural production in the municipalities of Belmonte and Ipiaú, Bahia states, Brazil - Bahia de Aguiar, Paulo César (2019)
The objective of this article is to compare and analyze the influence of rainfall patterns, in two distinct climatological normal periods (average monthly accumulation), on the agricultural production of the municipalities of Belmonte and Ipiaú, Bahia. For this, secondary socioeconomic data were collected for the socioeconomic characterization of the municipalities; historical series of rainfall data for the periods 1956 to 1987 and 1996 to 2017 (Belmonte) and 1950 to 1979 and 1980 to 2008 (Ipiaú). This led to the comparison and analysis of the two periods and the evolution of the main agricultural products of the municipalities, in order to identify the influence of rainfall patterns on agricultural production. It was verified that in Belmonte, during the majority of the period between the years 2004 to 2015, there was a decrease in the total rainfall profile, and the main agricultural products presented increasing or stable production. In Ipiaú, it was observed that rainfall peaks within the rainfall total were higher in the first period analyzed (1950 to 1979); and that excessive rainfall has negatively influenced some crops, especially the production of small and medium-sized farms. It can be inferred that for the periods analyzed, the rainfall pattern did not change much, and the changes observed did not affect the rainfall distribution throughout the year, remaining relatively well distributed.